Mokobang SDGP Website Analysis and Design - Moningkey,, Efraim R S; Triyono, Mochamad Bruri; Priyanto (International Journal of Information Technology and Education, 2022)
Valid and fast information is needed in everyday life. Information will be an important element in the development of society today and in the future, but the high need for information is sometimes not balanced with the presentation of adequate information. Often with the development of current information systems, SDGP Mokobang requires an identifier in the digital world that can also be used for promotion. In the development of SDGP Mokobang has never built a website that becomes a school information portal. By using the prototype method this research can be done quickly and according to the wishes of the user.